Signification of DNA integrity in sperm of Palaemon serratus (Pennant 1777): Kinetic responses and reproduction impairment. (February 2019) - Erraud, Alexandre; Bonnard, Marc; Geffard, Olivier; Coulaud, Romain; Poret, Agnès; Duflot, Aurélie; Forget-Leray, Joëlle; Geffard, Alain; Xuereb, Benoit
Abstract: The study of the effects of contamination on sperm quality not only provides an early, specific and integrative response to the fraction of bioavailable pollutants, but also has been shown to predict the potential of this fraction to modify an organism's capacity to reproduce. In addition, fertility damage in invertebrates has been addressed as a major problem that may pose a threat to the maintenance of populations. In this context, the present study proposes a methodology based on the measurement of sperm DNA integrity to evaluate the impact of paternal damaged DNA on the reproductive success of Palaemon serratus . A preliminary methodological optimization step was carried out to assess the kinetics of response of spermatozoa as well as the sensitivity of the spermatozoa according to their location in the genital tract. Spermatozoa appeared to be sensitive to a short in vivo exposure to the direct acting agent methyl methanesulfonate ( i.e. MMS; 2 days), with a persistence of damage even after a 30 days' recovery in a clean environment, suggesting a probable lack of DNA repair machinery. Moreover, our results revealed no difference in the level of DNA damage in mature spermatozoa whatever the exposure in spermatophore located in the terminal ampulla or in the proximal and distal part of the vas deferens. Finally, a significant decrease in the percentage of naturally bred prawns has been observed at the highest concentration of MMS ( i.e. 100 μM). Nevertheless, no reproduction impairment ( i.e. fertilization rate and early embryo development) following a paternal exposure has been shown in spite of very high levels of sperm DNA damage. In regard to the literature, this result raises questions concerning the kinetics of expression of genotoxic damage on progeny in the Palaemon model and future work will be led in this way. Highlights: Spermatozoa sensitivity of P. serratus to a short in vivo MMS exposure. Persistence of DNA damage after stress cancellation. No reproduction impairment following paternal exposure during embryonic development.